Disrupting Unwanted Habits in Online Gambling Through Information Technology - Hou, Jinghui; Kim, Keehyung; Kim, Sung S.; Ma, Xiao (Journal of Management Information Systems, 2019)
The instant access to gambling anytime, anywhere, has made online gambling highly habitual for some people. As a result, some online gamblers choose to volitionally enable the website-provided disruptive information technology (IT) features to control their gambling routines. The objective of this study is to examine the role of these features in regulating online gambling behavior. It is worthwhile to note that in this research, we do not make the assumption that habitual or regular online gambling is a bad thing; nor does the development of our conceptual framework — which focuses on the effect of disruptive IT features and moderating roles of individual regularity and game type in modifying gambling routines — depend on such an assumption.Drawing on theories of habitual automaticity and habit disruption, the conceptual framework theorizes the efficacy and mechanism of disruptive features while taking into account heterogeneity in individual regularity and game type. We tested the model using data collected over 10 years from 3,526 users of a gambling website. First, we found that individuals’ repetitive gambling patterns weakened as the duration of exposure to disruptive features increased. Second, the behavior of more regular gamblers was more resistant to the disruptive features, because more regular gamblers exhibited a stronger habitual pattern. Third, disruptive features were less effective on sports games compared with casino games, because sports gamblers tended to exhibit stronger gambling routines. Overall, the present study contributes to the information systems (IS) literature by clarifying how simple IT features may disrupt unwanted and difficult-to-break online gambling habits as judged by the gamblers. Our findings are likeliest to apply to broader areas of online services in which the application in question is integrated into everyday life and the system can offer a disruptive mechanism.